Can microbiologists help to assess catheter involvement in candidaemic patients before removal?. (10th December 2012) - Bouza, E.; Alcalá, L.; Muñoz, P.; Martín‐Rabadán, P.; Guembe, M.; Rodríguez‐Créixems, M.; Roilides, E.; ,
Abstract We compared the efficacy of three techniques—minimal time to positivity (MTTP) of blood cultures (BCs), differential time to positivity (DTTP) of BCs obtained from the catheter and peripheral veins and the number of positive BCs—in predicting catheter involvement in patients with well‐demonstrated catheter‐related candidaemia (C‐RC) and non‐catheter‐related candidaemia (NC‐RC).C‐RC was defined as isolation of the same Candida species from blood and catheter tip culture (≥15 cfu/plate). A ROC curve was created for each quantitative variable to determine the best cut‐off for predicting C‐RC.A total of 108 episodes of candidaemia were included (84 adults and 24 children; 67 C‐RC and 41 NC‐RC). These were caused mainly by C. albicans (49.1%) and C. parapsilosis (30.6%). The MTTP was significantly shorter in adult patients with C‐RC than in those with NC‐RC (29.8 vs. 36.8 hours; p 0.035), although no cut‐off value provided acceptable accuracy. DTTP had high sensitivity but low specificity for predicting CRC. However, C‐RC episodes had a significantly greater number of positive BCs than NC‐RC episodes. The optimal cut‐off for predicting C‐RC was at least two positive BCs out of three, with the following validity values: sensitivity, 100%; specificity, 62.5%; positive predictive value, 83.3%; negative predictive value, 100%; accuracy, 87.0%.None of the tests evaluated allow a clear‐cut prediction of C‐RC and the criteria accepted for bacteraemia should not be automatically extrapolated to candidaemia. We found that a low number of positive BCs with Candida had a high negative predictive value for a catheter origin.